2012
DOI: 10.1007/s00299-012-1298-9
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of rice leucine-rich repeat protein results in activation of defense response, thereby enhancing resistance to bacterial soft rot in Chinese cabbage

Abstract: Pectobacterium carotovorum subsp. carotovorum causes soft rot disease in various plants, including Chinese cabbage. The simple extracellular leucine-rich repeat (eLRR) domain proteins have been implicated in disease resistance. Rice leucine-rich repeat protein (OsLRP), a rice simple eLRR domain protein, is induced by pathogens, phytohormones, and salt. To see whether OsLRP enhances disease resistance to bacterial soft rot, OsLRP was introduced into Chinese cabbage by Agrobacterium-mediated transformation. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…We found the same characteristics in SLRR2 (Figure 2B and C). Two groups have reported that OsLRR1–a member of the family in rice–enhances disease resistance when ectopically expressed in Arabidopsis and Chinese cabbage [40], [43]. We therefore conclude that SLRR2 is a new member of the simple eLRR domain protein family and that SLRR and SLRR2 are involved in the defense response.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…We found the same characteristics in SLRR2 (Figure 2B and C). Two groups have reported that OsLRR1–a member of the family in rice–enhances disease resistance when ectopically expressed in Arabidopsis and Chinese cabbage [40], [43]. We therefore conclude that SLRR2 is a new member of the simple eLRR domain protein family and that SLRR and SLRR2 are involved in the defense response.…”
Section: Discussionmentioning
confidence: 57%
“…Recently, some groups have proposed that SLRR belongs to an LRR subfamily called the simple eLRR domain protein family [40][43]. Although members of the family are structurally similar to the LRR-only receptor PGIP, they show greater sequence identity to the LRR domains of receptor-like kinases such as SERK1, SERK2, and BAK1.…”
Section: Discussionmentioning
confidence: 99%
“…qRT-PCR analysis showed that B-deficient roots had enhanced expression of LRP , but decreased expression of sulfate transporter (Table 3). Park et al [83] observed that heterologous expression of rice LRP ( OsLRP ) resulted in the activation of defense response and enhanced resistance to bacterial soft rot in Chinese cabbage. Thus, the higher expression of LRP might partially compensate for the decreased disease resistance in B-deficient plants [66].…”
Section: Discussionmentioning
confidence: 99%
“…tomato DC3000 ( Pst DC3000) (Zhou et al 2009; Zhou et al 2010) and Pectobacterium carotovorum subsp. carotovorum (Park et al 2012) respectively. In contrast to these results, we found overexpression of LRR1 in the Kitaake rice variety did not enhance resistance to Xoo (Fig.…”
Section: Discussionmentioning
confidence: 99%